IMPLEMENTASI PROGRAM KELUARGA HARAPAN DI KOTA TANGERANG SELATAN - Dinata Firmansyah; Fentiny Nugroho (Politeknik Kesejahteraan Sosial Bandung, 2021)
This study attempts to describe the implementation of the Family Hope Program (PKH) in Sawah Baru Subdistrict, Ciputat District, Tangerang Selatan City, which is adjacent to Bintaro economic area in Tangerang Selatan City and the DKI Jakarta Province. A descriptive qualitative approach is utilised to understand the phenomena experienced by research subjects. Data collected through observation, indepth interviews, literature study and documentation. The result shows the implementation of PKH in relation to the graduation of PKH recipients (Keluarga Penerima Manfaat/KPM PKH) in Sawah Baru, is in accordance with the technical procedures and guidelines for social assistance program released in 2019. Moreover, coordination and relations between the local government and the designated work unit in fulfilling its duties and functions is also in accordance with Law Number 23 of 2014 on Local Government. In addition, to encourage the graduation and improve community welfare, the KPM PKH facilitators in Sawah Baru have several procedural strategies as well as personal strategies. The procedural strategies are as described in the PKH technical guidelines issued by the Ministry of Social Affairs, while the personal strategies are taken by adjusting the dimensions of its internal strength. However, the number of KPMs graduated is only 3-5 percent of the national target, since there is a lack of awareness of the KPM PKH to improve their status into a prosperous family.